2016
DOI: 10.1371/journal.pone.0164108
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Fungal Diversity and Community Composition in Two Closely Related Platanthera (Orchidaceae) Species

Abstract: While it is generally acknowledged that orchid species rely on mycorrhizal fungi for completion of their life cycle, little is yet known about how mycorrhizal fungal diversity and community composition vary within and between closely related orchid taxa. In this study, we used 454 amplicon pyrosequencing to investigate variation in mycorrhizal communities between pure (allopatric) and mixed (sympatric) populations of two closely related Platanthera species (Platanthera bifolia and P. chlorantha) and putative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…Roots of Platanthera bifolia were colonised by the Ceratobasidiaceae Thanatephorus fusisporus as in Esposito et al. (), and the germination mycobionts of P. bifolia overlapped with Thanatephorus but also hosted Ceratobasidiaceae and Tulasnellaceae.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Roots of Platanthera bifolia were colonised by the Ceratobasidiaceae Thanatephorus fusisporus as in Esposito et al. (), and the germination mycobionts of P. bifolia overlapped with Thanatephorus but also hosted Ceratobasidiaceae and Tulasnellaceae.…”
Section: Discussionmentioning
confidence: 74%
“…Seven orchid species known to be associated with rhizoctonia fungi as adults (Bidartondo et al., ; Esposito, Jacquemyn, Waud, & Tyteca, ; Jacquemyn, Brys, Cammue, Honnay, & Lievens, ; Jacquemyn et al., ; Oja, Kohout, Tedersoo, Kull, & Kõljalg, ; Stark, Babik, & Durka, ; Těšitelová et al., ) were chosen for the in situ seed sowing experiment and sampled together with autotrophic references at four sites in North‐East Bavaria for stable isotope natural abundance analysis (Table ): Dactylorhiza majalis (Rchb.) P.F.Hunt & Summerh.…”
Section: Methodsmentioning
confidence: 99%
“…Within the framework of our research devoted to Platanthera in Belgium (Esposito, Jacquemyn, Waud & Tyteca 2016), we here focus on the observation of moth visitors of two Platanthera species, namely P. bifolia (L.) Rich. and P. chlorantha (Custer) Rchb.…”
Section: Introductionmentioning
confidence: 99%
“…388 Population clustering showed a consistent pattern indicating two independent genetic clusters: P. bifolia 498 Bateman et al 2014), in a previous study (Esposito et al 2016), we showed that in our studied sympatric 499 populations, mycorrhizal fungi were most likely not directly involved in maintaining species boundaries.…”
supporting
confidence: 66%